2020
DOI: 10.24912/jm.v24i3.676
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Brand Awareness, Brand Image, and Brand Trust on Brand Loyalty

Abstract: The aim of this research is to examine the positive influence of brand awareness, brand image, and brand trust on brand loyalty. The coffee shop business in big cities in Indonesia is growing rapidly. Each coffee shop strives to show its uniqueness. This competition has resulted in them competing to increase competitiveness by using logos, symbols, unique names – or what is usually called a brand to become a differentiator among the competitors. This study was done in a quantitative manner. The data was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 28 publications
2
25
1
12
Order By: Relevance
“…The results also revealed that perceived quality and brand awareness/association are two important antecedents for brand trust. These findings seem different from a previous study by Khanlari et al (2015) but are consistent with the Bernarto et al (2020) study. Further, perceived quality and brand trust is the antecedents for brand loyalty, and these findings align with the studies by Krystallis and Chrysochou (2014) and Alhaddad (2015).…”
Section: Discussion and Findingscontrasting
confidence: 97%
See 2 more Smart Citations
“…The results also revealed that perceived quality and brand awareness/association are two important antecedents for brand trust. These findings seem different from a previous study by Khanlari et al (2015) but are consistent with the Bernarto et al (2020) study. Further, perceived quality and brand trust is the antecedents for brand loyalty, and these findings align with the studies by Krystallis and Chrysochou (2014) and Alhaddad (2015).…”
Section: Discussion and Findingscontrasting
confidence: 97%
“…Third, regarding brand trust antecedents, the results show that brand community developed on social media, perceived quality and brand awareness/association increase members’ trust in a brand, which is in line with the literature (Bernarto et al, 2020; Nilowardono et al, 2020; Ra’d Almestarihi et al, 2021).…”
Section: Discussion and Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…When seen from social and psychological perspectives, brand image is a situation possessed by goods in which customers have thoughts and perceptions about the brand that is important to consumers in making their decisions (Arifin et al, 2020). In other words, the brand image serves as the indicator via which we purchase Bernarto et al, (2020). Brand image is a mental representation that depicts how customers see a brand, comprising all aspects of identity, product character, and feelings and connections that develop in customers' thoughts Zia et al, (2021).…”
Section: Brand Imagementioning
confidence: 99%
“…Therefore, coffee shop business actors carry out various strategies and carry out various business innovations so as not to lose their customers. One of the business strategies that must be improved from the advantages that every coffee shop has is the quality of service (Suryawan, 2020).…”
Section: Young People In Medan Have Their Favorite Coffee Shopmentioning
confidence: 99%